Development of four wheels space-frame hybrid air motorcycle chassis - Ser, Beng Sian (2013)
This project presents the development of four wheels space-frame hybrid air motorcycle chassis. Studies were made to investigate the computational stress/strain analysis and fabricate the four wheel space-frame hybrid air motorcycle chassis. With the rapid growth of vehicle availability and usage on the road in recent year, the rate of pollution is increasing. To alleviate the problem, four wheels space-frame hybrid air motorcycle has been developed. The hybrid air motorcycle is one kind of hybrid vehicle. It needs a lightweight and strong chassis to support the weight of the engine, drive-train compartment, driver, and other overall packaging system. A whole new compact motorcycle chassis design was undergone a various type of testing simulation by using FEA software. The simulation data such as stress, strain, displacement and factor of safety (FOS) were utilized as a guideline to develop and fabricate a new design of four wheels space-frame hybrid air motorcycle chassis. As a conclusion, the objective was achieved where the simulation results show that the chassis design will not provide significant affect neither to the chassis structure nor the driver.